Pengaruh Persepsi Kemudahan Penggunaan, Kepuasan Wajib Pajak Dan Pemanfaatan Teknologi Terhadap Penggunaan E-Filing Bagi Wajib Pajak Orang Pribadi Di Kantor Pelayanan Pajak Pratama Tabanan - Reminiati, Ni Made Pendit; W, Rai Dwi Andayani (Hita Akuntansi dan Keuangan, 2025)
Taxes as a source of state revenue have a very important role in financing national development. This research aims to determine the influence of perceptions of ease of use, taxpayer satisfaction and use of technology on the use of E-Filling for individual taxpayers at the Tabanan Pratama Tax Service Office. The population in this study was individual taxpayers with a sample of 80 respondents. This research sample was taken using the Accidental Sampling method. Questionnaires are used as a data collection technique using a list of questions. The analysis techniques used are validity tests, reliability tests, classical assumption tests, multiple linear regression and model feasibility tests. The research results show that the perceived ease of use variable, the taxpayer satisfaction variable and the technology utilization variable have a positive effect on the use of e-filling